Research and Application of Cloud Computing and Big Data Technology in Intelligent Desktop Virtualization System - Xia, Honglei (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
By analyzing the design requirements of a secure desktop virtualization information system, this paper proposes the security virtualization technology of "whitelist" security mechanism, the virtualization layer security technology of optimized design, and the virtual machine security technology of resource and network layer isolation. On this basis, this paper constructs the overall architecture of the secure desktop virtualization information system. This paper studies the desktop virtualization technology research based on VMware using VMware server virtualization solution to transform and upgrade the traditional intelligent desktop virtualization system, improve server resource utilization rate, and reduce operation and maintenance costs.